2018
DOI: 10.3389/fimmu.2018.01845
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Characterization of a Chicken Embryo Model Infected With Duck Hepatitis A Virus Type 1

Abstract: Duck hepatitis A virus type 1 (DHAV-1) is one of the most common and lethal pathogens in young ducklings. Live-attenuated DHAV vaccine (CH60 strain) developed by passaging in chicken embryos provided effective immune protection for ducklings. However, the accurate mechanism for such adaption in chicken embryos is not fully revealed. Here, we utilize RNA-sequencing to perform global transcriptional analysis of DHAV-1-innoculated embryonated livers along with histopathological and ultrastructural analysis. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
(47 reference statements)
3
17
0
Order By: Relevance
“…In the susceptible ducklings, the apoptosis rate was significantly higher than that in the resistant group. Previous studies found that duck hepatitis A virus type 1 (DHAV-1) caused apoptosis in the liver after infection (38)(39)(40). In agreement with previous studies, the DHAV-1 infection drove apoptosis in the liver and the inflammatory response to viral infection could have exacerbated the level of apoptosis.…”
Section: Discussionsupporting
confidence: 82%
“…In the susceptible ducklings, the apoptosis rate was significantly higher than that in the resistant group. Previous studies found that duck hepatitis A virus type 1 (DHAV-1) caused apoptosis in the liver after infection (38)(39)(40). In agreement with previous studies, the DHAV-1 infection drove apoptosis in the liver and the inflammatory response to viral infection could have exacerbated the level of apoptosis.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have shown that chicken embryos can be used as an animal model for DHAV-1 (16). However, there is no report of DHAV-1 infection in CEFs.…”
Section: Resultsmentioning
confidence: 99%
“…The changes in attenuated vaccines and virulent strains in the host before and after adaptation are also worthy of attention. Through transcriptome sequencing, we have found that attenuated vaccines induce type I and II interferon responses, activate innate immune responses, and simultaneously enhance the expression of SOCS1 and SOCS3 (16). We suspected that the adaptation of attenuated vaccines during the process of serial passage is related to high expression of SOCS proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations